Factors accelerating time to death among persons with Tuberculosis in Western India: Evidence from a community-based retrospective death audit - Harsh Shah; Jay Patel; Somen Saha; Bhavesh Modi; Pankaj Nimavat (PLoS ONE, 2026)
Introduction Tuberculosis (TB) remains a leading cause of death globally. India aims to eliminate TB by 2025; however, persistently high mortality rates suggest critical failures in early intervention, particularly among vulnerable populations. This study examined the clinical, social, and system factors associated with accelerated mortality among notified persons with TB (PwTB) in Western India. Methods A cross-sectional study was conducted in six districts of Gujarat, India, during 2023–2024 using Community-Based Verbal Autopsy (CBVA) among relatives of 149 deceased PwTB. Sociodemographic, clinical, and TB care cascade data were collected, and a retrospective time-to-event analysis was performed. A Cox proportional hazards model was used to assess the factors associated with a shorter time from diagnosis to death. Results Majority of deceased belonged to 26–50 years age group (40%), with a high male predominance (81.9%). Nearly half (48.3%) had comorbidities, and 65.8% had a history of addiction. A substantial median delay of approximately five weeks was observed between symptom onset and treatment initiation. Following a confirmed diagnosis, the majority of deaths (nearly 80%) occurred within the first 16 weeks. A comparable trend was noted after the start of treatment, with about 78% of fatalities occurring within 15 weeks. In the adjusted Cox regression model, key population status (HR = 1.5, p = 0.01), presence of comorbidities (HR = 2.0, p < 0.001), and drug-resistant tuberculosis (HR = 1.7, p = 0.003) were independently associated with a shorter time from diagnosis to death. Discussion The findings highlighted the convergence of clinical complexity, social vulnerability, and persistent system constraints that shorten survival, even after treatment initiation. Strengthening early case diagnosis, integrating comorbidity management, improving health system responsiveness, and implementing targeted strategies for vulnerable populations are critical. A systematic TB Death Surveillance and Response System (TBDSR), integrating facility-, community-based reviews, and digital reporting, would provide actionable insights to inform timely intervention and support progress towards TB elimination in India and other high-burden settings.